The incarnation as God's first intention: supralapsarian Christology for faith and practice - Driel, Edwin Chr. van (Baker Academic, a division of Baker Publishing Group, 2025)
"Though most Christians today would describe the incarnation of Jesus as God's response to sin, this book argues that God decided to become incarnate before humans sinned. This view has implications for both the doctrine and the practice of the church"-- Provided by publisher